ASN PERFORMANCE TRANSFORMATION: THE STRATEGIC ROLE OF CAREER DEVELOPMENT AND DIGITAL LEADERSHIP IN THE BPKAD OF CENTRAL SULAWESI PROVINCE - Abrar; Niluh Putu Evvy Rossanty; Bakri Hasanuddin; Nur Risky Islianti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study analyzes how employee performance at the Regional Financial and Asset Management Agency (BPKAD) of Central Sulawesi Province is influenced by career development and digital leadership. The challenges of digital transformation, which require public organizations to improve their work effectiveness and emphasize the importance of human resources for organizational success, are the background of this study. This study uses a quantitative method, and the population consists of 127 employees. 100 respondents are the research sample selected randomly using the simple random sampling method. Data were collected through observation and questionnaire distribution, reliability tests, validity tests, classical assumptions, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R2) were used to analyze it. The results show that career development has a positive and significant impact on employee performance and digital leadership has a positive and significant impact on employee performance. Simultaneously, both variables have a significant effect on career development. Together, these two variables contribute 84.1% to the variation in employee performance, while the remaining 15.9% is influenced by other variables not included in the research model.